Opportunities of Artificial Intelligence for Authentication and Assurance of Halal Products - Mahmudy, Wayan; Kurnianingtyas, Diva (Journal of Information Technology and Computer Science, 2025)
The need for Muslims to obtain halal food encourages the development of systems that can assist in the authentication and assurance of halal products. Various Artificial Intelligence (AI) based systems have been developed to meet these needs. AI is a technology that enables computers to understand, learn, and perform tasks that would typically require human intelligence and reasoning to act and make decisions. With the help of high-speed computers, AI algorithms learn patterns in available data and perform assigned tasks with high accuracy and efficiency. This study focusses on the application of AI for the identification, monitoring, verification and validation of halal products. Also, this paper limits the discussion to food products with the topics of (1) Inspection of raw materials and detection of contamination to ensure the halalness of raw materials (2) Market monitoring and recommendation of halal restaurants to help Muslim consumers. The consumers were looking for a restaurant that suits their needs and preferences (3) Verification of halal certification to ensure that the certification given to the product comes from a competent and trustworthy authority.